2017
DOI: 10.3390/rs9030233
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Land Cover and Seasonal Variation on Maximum Air Temperature Estimation Using MODIS Imagery

Abstract: Abstract:Daily maximum surface air temperature (Tamax) is a crucial factor for understanding complex land surface processes under rapid climate change. Remote detection of Tamax has widely relied on the empirical relationship between air temperature and land surface temperature (LST), a product derived from remote sensing. However, little is known about how such a relationship is affected by the high heterogeneity in landscapes and dynamics in seasonality. This study aims to advance our understanding of the ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Point observations are common in SWC studies on the plateau (Yang et al, ), having the advantages of high precision and temporal resolution but the disadvantage of weak spatial representativeness. Remote sensing has been an important method for acquiring data in studies with large areas (Cai, Chen, Wang, & Yang, ; Guo et al, ; Guo et al, ; Huang et al, ; Li, Bing, & Jin, ; Sun et al, ; Tian & Sun, ; Wang et al, ; Wang, Zhang, Qiu, et al, ). It has the advantages of being nondestructive, large scale, and independent of weather but is strongly influenced by land surface roughness and meteorological condition.…”
Section: Introductionmentioning
confidence: 99%
“…Point observations are common in SWC studies on the plateau (Yang et al, ), having the advantages of high precision and temporal resolution but the disadvantage of weak spatial representativeness. Remote sensing has been an important method for acquiring data in studies with large areas (Cai, Chen, Wang, & Yang, ; Guo et al, ; Guo et al, ; Huang et al, ; Li, Bing, & Jin, ; Sun et al, ; Tian & Sun, ; Wang et al, ; Wang, Zhang, Qiu, et al, ). It has the advantages of being nondestructive, large scale, and independent of weather but is strongly influenced by land surface roughness and meteorological condition.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figures 7-9, land cover contributed little in most of the climates. This seems to contradict other work (e.g., [31,33,65]) that confirmed the noticeable impacts of land cover on Tmax estimation as the specific heat varies significantly from one land cover type to another [31,33,65]. Nevertheless, Benali et al [12] and Janatian et al [32] indicated the independence of land cover when estimating Ta based on remote sensing data.…”
Section: Variable Importance Analysismentioning
confidence: 86%
“…At a local scale, many previous studies reported different relationships between Ta and LST and reached divergent or even contradictory conclusions in studies, e.g., if the land cover plays an important role in Ta estimation or not [12,[31][32][33][34] and if nighttime LST can outperform in daily maximum Ta than daytime LST estimation or not [12,[31][32][33][34]. For example, usually, daytime and nighttime LST is expected to be more effective and simply used in estimating daily maximum and minimum Ta (hereafter Tmax and Tmin), respectively [12,[31][32][33][34], as the observation time of daytime and nighttime LST from MODIS is close to the occurrence of the maximum and minimum LST and Ta, respectively. However, Zhang et al [35] and Zeng et al [4] showed that using nighttime LST resulted in higher accuracy Tmax estimations than using daytime LST.…”
mentioning
confidence: 98%
“…Many phenological studies have predicted plant phenology using LST (e.g., Chen et al 2018;Hanes and Schwartz 2011;Zhang et al 2004), often because LST is readily available from remote sensing imagery whereas air temperature is measured at sparsely-located weather stations. While air and land surface temperature are well correlated (Cai et al, 2017;Mildrexler et al, 2011), there is also a direct mechanistic link between LST and phenology: LST is directly related to energy exchanges between the atmosphere and soil (Quattrochi and Luvall, 1999;SimĂł et al, 2018) and soil temperature affects root phenology and plant reproductive phenology (Chen et al, 2016;Delpierre et al, 2016;Greer et al, 2006). LST measured by MODIS sensors on the Aqua and Terra satellites was extracted for each site (using coordinates of the site centroid) during each month from 2007 through 2017 and then reprojected to WGS84.…”
Section: Remote Sensing Datamentioning
confidence: 99%